2023
DOI: 10.3389/fpubh.2023.1025778
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the trajectory of obesity indicators on the age of pubertal onset and pubertal tempo in girls: A longitudinal study in Chongqing, China

Abstract: ObjectiveThis study aims to explore the influence of the trajectory of obesity indicators on the onset age of different pubertal development characteristics and pubertal tempo among girls.MethodsOur longitudinal cohort study recruited 734 girls at baseline in May 2014 from a district of Chongqing and followed them at 6-month intervals. Data were available from baseline to the 14th follow-up with a full record of height, weight, waist circumference (WC), breast development, pubic hair, and armpit hair developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Therefore, this study adopted purpose-based sampling in the district and selected four primary schools in the district of Chongqing according to the differences in their geographical locations. A detailed description of this cohort study has been reported previously ( 24 ). The study was approved by the Medical Ethics Review Committee of Chongqing Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this study adopted purpose-based sampling in the district and selected four primary schools in the district of Chongqing according to the differences in their geographical locations. A detailed description of this cohort study has been reported previously ( 24 ). The study was approved by the Medical Ethics Review Committee of Chongqing Medical University.…”
Section: Methodsmentioning
confidence: 99%